Fuzzy Analytic Hierarchy Process Evaluation Method in Assessing Corrosion Damage of Reinforced Concrete Bridges - Gao, Zhicheng; Li, Jiliang (Civil Engineering Journal, 2018)
Effective method used to deal with the corrosion damage condition of any concrete bridge superstructure will help decision makers of bridge management agencies to better choose repair material, and optimize repair method. Simplified corrosion index (SCI) is a very useful and simple index to characterize the actual corrosion damage condition of a reinforced concrete bridge superstructure. In this paper, SCI is calculated by combining the Corrosion Damage Index (CDI), Environment Change Factor (ECF) and Material Vulnerability Factor (MVF). The Analytic Hierarchy Process (AHP) method is applied to decide the weight factors of CDI, ECF and MVF. The Fuzzy-AHP evaluation method is used in this study to deal with the fuzzy problem of differentiating the different levels of corrosion indicators and to determine the appropriate weight factors. The asymmetric nearness degree method is applied to re-analyze the evaluation vector from Fuzzy-AHP method to calculate the corrosion damage level based on all corrosion indicators. A numerical example was presented to demonstrate the procedure and the benefits of the AHP method, and the proposed Fuzzy-AHP approach, along with the asymmetric nearness degree method, in dealing with the fuzzy nature of SCI calculation problem.